Price setting in the euro area: some stylized facts from individual consumer price data - Emmanuel Dhyne; Luis J. Álvarez; Hervé Le Bihan; Giovanni Veronese; Daniel Dias; Johannes Hoffmann; Nicole Jonker; Patrick Lünnemann; Fabio Rumler; Jouko Vilmunen (European Central Bank (ECB), 2005)
This paper documents patterns of price setting at the retail level in the euro area, summarized in six stylized facts. First, the average euro area monthly frequency of price adjustment is 15 p.c., compared to about 25 p.c. in the US. Second, the frequency of price changes is characterized by substantial cross product heterogeneity - prices of oil and unprocessed food products change very often, while price adjustments are less frequent for processed food, non energy industrial goods and services. Third, cross country heterogeneity exists but is less pronounced. Fourth, price decreases are not uncommon. Fifth, price increases and decreases are sizeable compared to aggregate and sectoral inflation rates. Sixth, price changes are not highly synchronized across retailers. Moreover, the frequency of price changes in the euro area is related to several factors, such as seasonality, outlet type, indirect taxation, pricing practices as well as aggregate or product specific inflation.
Keywords: E31; D40; C25; 330; consumer price; frequency of price change; Pricesetting; Einzelhandelspreis; EU-Staaten